Effects of pre-cooling on thermoregulation and endurance exercise - Ückert, S.; Joch, W. (New Studies in Athletics, 2005)
Warm and humid climatic conditions have a negative effect on endurance performance. The classic strategy to tackle the problem from a performance perspective is twofold: compensation of the organism`s negative water balance and optimisation of the adaptation mechanisms to high ambient temperatures. However, because these strategies have only limited effects and because they do not decisively affect the heat-induced decrease in performance, further means have been discussed and, to a certain extent, put into practice in an effort to improve the heat tolerance of top-level athletes. A number of researchers, coaches and athletes have explored the possibility of cooling the body prior to exercise, thorough the use of cooling jackets and other items worn by the athlete and through the use of cooling chambers, as a means to improve endurance performance. This article discusses the fundamentals of pre-cooling and summarises key studies on the technique conducted to date. The authors conclude that external cooling is a sensible and necessary means to avoid or attenuate the performance-reducing effects of heat in endurance sports.